Nationalism and development in Asia - Prasenjit Duara (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
This paper identifies historic patterns in the dialectic between nationalism and development across various East, South, and Southeast Asian nations. Nationalism as the rationale for development is used by regimes to achieve high levels of growth, but also generates exclusivism and hostilities, often in order to integrate a political core. Popular nationalism has also dialectically reshaped the goals and patterns of development during the post-Second World War period. The region is divided into zones shaped by twentieth-century historical and geo-political conditions. Colonial and Cold War conditions were as important as internal political and ethnic circumstances. Turning points in the dialectical relationship were common within a region. More recently, a common transregional pattern has emerged with neoliberal globalization being accompanied by exclusivist nationalism.
Keywords: 330; Cold War; colonialism; development; exclusivism; nationalism; region; regionalism